Endoscopic bile drainage - Gutiérrez Galiana, Horacio; Taullard, Daniel; Kliche, Ivanah (Cirugía del Uruguay, 1991)
lnitial experience in endoscopic drainage of biliar viae is presented. Two techniques were used: externa/ EBD with nasobi/iar probe in two patients and interna/ EBD or endoprosthesis en 3 cases. In the two externa/ EBD cases the indication was cholangitis due to lithiasis. Interna/ EBD was employed in a case of biliar viae stenosis due to pancreatic neoplasm in one case and due to ga/1-bladder neoplasm in another, and a case of choledochal lithiasis with surgica/ counterindications. Very good initial results were obtained for externa/ EBD in cholangitis and interna/ EBD in neop/asms. Long-termaresults in this last group must be eva/uated.